Characterization of nitrogen-fixing and IAA-producing purple non-sulfur bacteria isolated from rice fields in Nam Dinh, Vietnam - Lien, Do Thi; Ngoc Mai, Cung Thi; Thu Hang, Dinh Thi; Thi mai, Tran; Kim Tien, Nguyen Thi; Nhi Cong, Le Thi; Kim Anh, Bui Thi; Ngoc Minh, Nghiem (Academia Journal of Biology, 2026)
This study aimed to select purple photosynthetic bacteria (PPB) isolated from various paddy fields, including saline fields in Giao Thuy and paddy fields in Y Yen, based on their biofertilizer properties. Among 24 PPB isolates, strains GT10 and Y11 exhibited the highest efficiency in indole-3-acetic acid (IAA) production and nitrogen fixation. GT10 colonies were circular and convex, with smooth surfaces, reddish brown, diameter: 0.9-1.2 mm. The cell suspension appeared reddish-brown. Colonies of strain Y11 were spread out, reddish brown, slimy, diameter: 1.8-2.2 mm, with a purple-colored cell suspension. GT10 cells were oval-shaped (0.9-1.25 μm long, 0.6-0.7 μm wide) and reproduced by binary fission. In contrast, Y11 cells were rod-shaped (1.4-1.58 μm long, 0.36-0.441 μm wide) and reproduced by budding. Elemental sulfur globules were not observed in either strain. Both were Gram-negative and contained bacteriochlorophyll a as their primary photosynthetic pigment. The GT10 strain was able to use carbon sources such as acetate, propionate, lactate, succinate, formate, citrate, mannitol, sorbitol, glycerol, glutamate, isopropanol, sulfide, but not tartrate, methanol, or ethanol. These characteristics are consistent with the genus Rhodobacter. Y11 strain was able to use carbon sources such as acetate, propionate, lactate, succinate, formate, citrate, mannitol, sorbitol, glycerol, glutamate, or sulfide, but did not utilize tartrate, methanol, ethanol, or isopropanol. These capacities are similar to those of the Rhodopseudomonas species. Based on 16S rDNA sequencing, strain Y11 was identified as Rhodopseudomonas palustris, while strain GT10 was Rhodobacter capsulatus. The combined application of GT10 and Y11 strains may offer a sustainable biofertilizer alternative to chemical fertilizers in rice cultivation.